1979
DOI: 10.4141/cjas79-084
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Level of Feeding on Breeding Performance and Conceptus Development at 60 Days of Pregnancy in the Gilt

Abstract: For personal use only.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1991
1991
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Low plane feeding, however, does not appear to have such negative effects. Anderson (1975), Dyck (1991) and Dyck & Strain (1979) found no effect of low plane feeding commencing fiom as early as 35 days before mating and continuing throughout early pregnancy on embryo survival. We have recently examined the effects of different planes of nutrition, both before and after mating, on embryo survival and function on day 12 (Ashworth et al 1995(Ashworth et al , 1996.…”
Section: Effects Of Nutrition On Embryo Survival and Growth (I) Spec@mentioning
confidence: 92%
“…Low plane feeding, however, does not appear to have such negative effects. Anderson (1975), Dyck (1991) and Dyck & Strain (1979) found no effect of low plane feeding commencing fiom as early as 35 days before mating and continuing throughout early pregnancy on embryo survival. We have recently examined the effects of different planes of nutrition, both before and after mating, on embryo survival and function on day 12 (Ashworth et al 1995(Ashworth et al , 1996.…”
Section: Effects Of Nutrition On Embryo Survival and Growth (I) Spec@mentioning
confidence: 92%
“…In the production of replacement gilt, increasing the energy supply of the diet would make the replacement gilts grow quickly to meet the breeding standard as soon as possible ( 17 , 18 ), but it will cause excessive obesity of the gilts, which often leads to mammary gland fat deposition and dysplasia, affecting milk production; furthermore, it has adverse effects on the lactation function in the later period ( 10 ). However, the question is how to balance the high-energy needs of gilts for rapid development and the adverse effects of excessive energy on mammary gland development.…”
Section: Introductionmentioning
confidence: 99%
“…Throughout vertebrates the onset of estrus indicates that the female organism has reached sufficient sexual maturity to reproduce. Studies have shown that reproductive function in pigs is sensitive to the status of energy reserves suggesting that weight loss in humans by extreme dieting methods may have potential negative effects on fertility [ 1 3 ]. Nutritional factors are the strongest and most obvious environmental factors affecting the timing of puberty [ 4 ], and studies have revealed that nutrient restriction in post-pubertal gilts led to cessation of estrus [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Nutritional status, especially overall energy level, is important for the onset of estrus [ 1 3 , 5 ]. Depressed luteinizing hormone (LH) and follicle stimulating hormone (FSH) secretion led to the inhibition of gonadal function and reproductive failure in nutrient restricted animals [ 2 ].…”
Section: Introductionmentioning
confidence: 99%